Breast cancer resistance protein (BCRP) and excision repair cross complement-1 (ERCC1) expression in esophageal cancers and response to cisplatin and irinotecan based chemotherapy - Bharthuar, Anubha (Pioneer Bioscience Publishing Company, 2014)
BACKGROUND: Esophageal cancer patients face a dismal outcome despite tri-modality management and median survival remains 15-18 months. Breast cancer resistance protein (BCRP) is an ATP-dependent efflux protein associated with chemotherapy resistance. The role of BCRP expression in esophageal cancer and normal esophageal cells is not known. Excision repair cross complement-1 (ERCC1) overexpression has been correlated with poorer response to cisplatin based chemotherapy. We examined the expression of BCRP and ERCC1 in patients with esophageal cancer and correlated it with survival in patients receiving irinotecan and cisplatin based chemotherapy. METHODS: With IRB approval, 40 cases of esophageal cancer diagnosed from 2004-2008, were stained for BCRP and ERCC1 expression by immunohistochemistry and scored by a pathologist blinded to clinical data. Baseline demographics, therapy given and survival data were collected and correlated with BCRP and ERCC1 expression. Fisher’s exact test was used to determine association between BCRP and ERCC1 expression and demographics. Cox proportional hazards model was used for association of BCRP and ERCC1 with survival. RESULTS: On immunohistochemistry, 30/40 cancers (75%) expressed BCRP. Interestingly, down-regulation of BCRP expression in tumor compared with normal cells was seen in 40% of patients. ERCC1 positivity was seen in 15/30 cases (50%). Median overall survival (OS) was 19 months with no difference in survival between BCRP positive and negative patients (P=0.13) or ERCC1 positive and negative patients (P=0.85). Estimated hazard ratio (HR) of death for BRCP positive patients was 2.29 (95% CI: 0.79-6.64) and for ERCC1 positive patients was 1.09 (95% CI: 0.46-2.56). There was no association of BCRP and ERCC1 expression with disease stage, age, gender or histology. For patients who received cisplatin and irinotecan as first line chemotherapy, there was no difference in survival based on BCRP or ERCC1 status. CONCLUSIONS: BCRP expression is seen in a majority of esophageal cancers and normal esophageal mucosa. ERCC1 expression is seen in about half of the patients with esophageal cancer. Irinotecan based studies with esophageal and gastric cancer suggest response rates of 14-65%. Whether the 40% of tumors in our study found with down regulation of BCRP expression, constitute a majority of these responders needs to be prospectively validated in a larger data set. It should include markers such as ERCC1 predicting response to 5-fluorouracil and platinum based chemotherapy, to enable individualizing therapy for this cancer.